ANALISIS STRATEGI GMF POWER SERVICES SEBAGAI SALAH SATU SBU GMF DALAM MENCIPTAKAN COMPETITIVE ADVANTAGE PADA PERSAINGAN INDUSTRI JASA OVERHAUL GAS TURBINE ENGINE - , Budi Rimpan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to learn the factors that affect the internal and external capabilities of GMF Power Services as a Strategic Business Unit of GMF AeroAsia in creating competitive advantage in the service industry maintenance and overhaul of gas turbine engines in Indonesia. Competitive strategy analysis is done by evaluating the strategies that have been implemented by the GMF Power Services and formulate new strategies and suggest it that can be applied by the GMF Power Services to face the competition in the future. The study was conducted by analyzing the external and internal environment that may affect the company which then coupled with a SWOT analysis. From the analysis of the external environment are summarized in a SWOT analysis of opportunities and threats in mind that the care services industry and overhaul of gas turbine engines is influenced by a number of industrial users of gas turbine engine itself in terms of market demand, the need for maintenance of gas turbine engines from industry, government policies, corporate competitors, the company's suppliers of parts and service product substitution. While the results of internal environmental analysis is summarized in the SWOT as a strength and weakness of factors obtained results that are qualified experts, the company's reputation, the ease of building a network, product quality standards and excellence of the value chain into a major force for the company. While the availability of a major asset in the form of a test cell and engine maintenance capacity is still relatively low, a factor of weakness for the company. Conclusions can be drawn from the results of this study is that in company development, GMF Power Services found several obstacles encountered, one of which is the procurement of assets in the form of test cell as the main asset that must have when they want to compete in the industrial gas turbine overhaul engine. It is necessary for companies to pursue this test cell in order to remain competitive in this industry. Business unit synergy strategy adopted by the GMF Power Services in the value chain is properly applied so that the company was able to survive and create a competitive advantage compared with similar companies and the policy issued by the government to raise local content have a positive impact for the company. This is evident from the opportunities gained by GMF Power Services when they get the job to handling several machine of gas turbine engine with a few big companies in Indonesia.